Science and the economic order (Frankfurt am Main, 1956)
The goverment giving a contract for the construction of a large bridge, without calling upon the services of engineers and technologists who received their training at universities and colleges where they studied mechanics and other branches of physics, in addition to the mathematics and chemistry.